Black Lives Matter and Music : Protest, Intervention, Reflection - Maultsby, Portia K.; Shonekan, Stephanie; Orejuela, Fernando (Book collections on Project MUSE., 2018)
Music has always been integral to the Black Lives Matter movement in the United States, with songs such as Kendrick Lamar's "Alright," J. Cole's "Be Free," D'Angelo and the Vanguard's "The Charade," The Game's "Don't Shoot," Janelle Monae's "Hell You Talmbout," Usher's "Chains," and many others serving as unofficial anthems and soundtracks for members and allies of the movement. In this collection of critical studies, contributors draw from ethnographic research and personal encounters to illustrate how scholarly research of, approaches to, and teaching about the role of music in the Black Lives Matter movement can contribute to public awareness of the social, economic, political, scientific, and other forms of injustices in our society. Each chapter in Black Lives Matter and Music focuses on a particular case study, with the goal to inspire and facilitate productive dialogues among scholars, students, and the communities we study. From nuanced snapshots of how African American musical genres have flourished in different cities and the role of these genres in local activism, to explorations of musical pedagogy on the American college campus, readers will be challenged to think of how activism and social justice work might appear in American higher education and in academic research. Black Lives Matter and Music provokes us to examine how we teach, how we conduct research, and ultimately, how we should think about the ways that black struggle, liberation, and identity have evolved in the United States and around the world.